The impact of ESG performance on corporate innovation—Empirical evidence from Chinese pharmaceutical listed companies - Liqiang Li; Su Wang; Yuwen Chen (PLoS ONE, 2025)
Environmental, social and governance performance is an important driver for companies to achieve innovative and high-quality development, and the relationship between sustainable development and corporate innovation is one of the key concerns of pharmaceutical companies. This study aims to reveal the intrinsic role mechanism of sustainable transformation of pharmaceutical enterprises in high-quality innovation development. Based on the relevant data of China’s A-share pharmaceutical listed companies from 2015 to 2022, the study establishes a fixed effect model and a mediation effect model, empirically examines the impact of ESG performance on the innovation of pharmaceutical listed companies, and deeply explores the role mechanism of R&D personnel investment and government subsidies in it. The study finds that: (1) ESG performance significantly enhances firms’ innovation inputs and green innovation outputs; (2) this facilitating effect is more substantial among non-state-owned firms and firms in the eastern region; (3) good ESG performance has a more pronounced facilitating effect on innovation inputs of large firms, while it has a more prominent effect on the green innovation outputs of small and medium-sized firms; and (4) the mechanism analysis indicates that internal R&D personnel investment and external government subsidies play a significant mediating effect between ESG performance and corporate innovation. This study provides new empirical evidence for understanding the mechanism of ESG performance on corporate innovation in Chinese pharmaceutical companies. It provides theoretical support for proactively promoting the sustainable transformation and deepening the development of green innovation in Chinese pharmaceutical companies. In addition, there are important policy implications for promoting the sustainable transformation of pharmaceutical companies: the establishment of differentiated ESG incentive policies, the improvement of R&D talent training mechanisms, and the optimization of government subsidy allocations, focusing on supporting green innovation by companies with excellent ESG performance.